2021
DOI: 10.1101/2021.02.17.21251957
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Change in vaccine willingness in Australia: August 2020 to January 2021

Abstract: The ANU Centre for Social Research and Methods ANU COVID-19 Impact Monitoring Survey Program asked the same group of respondents about their vaccine intentions in August 2020 and January 2021. The paper provides data on the vaccine willingness in Australia as of January 2021 and how this changed since August 2020 both at the national level and for particular individuals. The paper provides estimates of how vaccine willingness has changed for different population sub-groups and the individual level characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
83
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(99 citation statements)
references
References 11 publications
13
83
3
Order By: Relevance
“…Both of these vaccines have demonstrated high clinical efficacy [4,5] . However, between August 2020 and January 2021, there has been a substantial increase in vaccine hesitancy in Australia, with 21.7% of surveyed Australians responding that "they probably or definitely would not get a safe and effective COVID-19 vaccine in January 2021" [6] . Furthermore, over April-June 2021, the vaccine rollout strategy in Australia has been significantly revised due to health risks attributed to administering the ChAdOx1 nCoV-19 (Oxford/AstraZeneca) vaccine to individuals in specific age groups.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these vaccines have demonstrated high clinical efficacy [4,5] . However, between August 2020 and January 2021, there has been a substantial increase in vaccine hesitancy in Australia, with 21.7% of surveyed Australians responding that "they probably or definitely would not get a safe and effective COVID-19 vaccine in January 2021" [6] . Furthermore, over April-June 2021, the vaccine rollout strategy in Australia has been significantly revised due to health risks attributed to administering the ChAdOx1 nCoV-19 (Oxford/AstraZeneca) vaccine to individuals in specific age groups.…”
Section: Introductionmentioning
confidence: 99%
“…While studies have consistently found that COVID‐19 has impacted negatively on Australians’ mental health, 4 , 5 , 6 , 7 , 8 to date there is no evidence of an accompanying increase in suicides. Analysis of the Queensland Suicide Register data found there was no overall change to the suicide rate for Queensland during the seven months following its 29 January 2020 Public Health Emergency Declaration in response to COVID‐19.…”
mentioning
confidence: 99%
“…Vaccination willingness was reported as 85.8% in April 2020 2 (n=4362, with vaccination reluctance associated with low health literacy and lower education level) and 75% in June 2020 (n=2018) 3 . These suggest a progressive decline in vaccination willingness over time; Biddle et al 4 reported that at an individual level, 31.9% of the 2737 Australians they surveyed became less willing to get the vaccine between August 2020 and January 2021.Vaccine hesitancy may have increased since then with recent publicity about adverse effects such as clotting.…”
mentioning
confidence: 99%